Spatial Data Modelling for 3D GIS - Abdul-Rahman, Alias; Pilouk, Morakot; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
This book covers fundamental aspects of spatial data modelling specifically on the aspect of three-dimensional (3D) modelling and structuring. Realisation of "true" 3D GIS spatial system needs a lot of efforts, and the process is taking place in various research centres and universities in some countries. The development of spatial data modelling for 3D objects is the focus of this book. The book begins with some problems and motivations, the fundamental theories, the implementation, and some applications developed based on the concepts. The book is intended for various geoinformation related professionals like GIS engineers, GIS software developers, photogrammetrists, land surveyors, mapping specialists, researchers, postgraduate students, and lecturers.
An Overview of 3D Gis Development -- 2D and 3D Spatial Data Representations -- The Fundamentals of Geo-Spatial Modelling -- The Conceptual Design -- The Logical Design -- Object-Orientation of Tins Spatial Data -- The Supporting Algorithms -- Applications of the Model -- The Web and 3D Gis -- Conclusion and Further Outlook.
Keywords: Geography; Geophysics; Computers; Geographical information systems; Remote sensing; Regional planning; Urban planning; Physical geography; Geography; Geographical Information Systems/Cartography.; Information Systems and Communication Service; Geophysics/Geodesy.; Remote Sensing/Photogrammetry.; Physical Geography; Landscape/Regional and Urban Planning; Electronic books